Metodologia espaço-temporal para a análise de antenas impressas - Virgilio Ribeiro Mota (2010)
This work presents a methodology based on Finite-Difference Time-Domain Method (FDTD) which allows analyzing and studying about microstrip antennas behavior in many directions by near-field to far-field transforms. This process modify an algorithm developed by Silva in order to obtain tangential electric and magnetic fields to closed surface in time domain, by applying Surface Equivalence Theorem and, if necessary, reducing ground plane of antenna. Farfields are obtained from near-field, using Multilevel Surface Decomposition Method (MSD), with code developed in FORTRAN and printed antennas radiation diagramsare generated in MATLAB. A form of validation to this methodology was generating irradiation diagrams to frequency domain, since frequency/time domains can be compared with a reference solution based on the Cavity Method, which code was developed in MATLAB environment. Besides of this, it was developed a code in MATLAB to determine printed antennas return loss, in order to calculate and to visualize scattering parameter or return loss using Moment-Expansion Deconvolution Method.